Assessing students with special needs - McLoughlin, James A.; Lewis, Rena B. (Upper Saddle River, New Jersey : Pearson Education, 2008)
This popular resource presents comprehensive, accessible, balanced coverage of both formal and informal assessment for learners with disabilities. Grounded in the idea that assessment is at the center of all good teaching, this comprehensive text is noted for its accessibility and its thorough exploration of the link between gathering information and actually using it to make informed decisions. In it, readers get a solid understanding of the complete assessment process, from choosing the best tool, to adapting instruction, to improving outcomes. Included is coverage of both popular and lesser-known tools, giving readers promising procedures for assessing students with special needs. The new edition includes embedded videos, introductory learning objectives, summary learning objectives, breakpoint practices, multimodal methodology, and updating throughout including assessments, research articles, examples, figures, and legal information. The Enhanced Pearson eText features embedded videos, self-check assessments, and interactive exercises.
Part 1. Introduction to special education assessment -- 1. Special education assessment -- 2. The assessment process -- Part 2. Skills for special educators -- 3. Selection of assessment tools -- 4. Standardized tests -- 5. Classroom assessment -- Part 3. Assessment for special education eligibility -- 6. Academic achievement -- 7. Intellectual performance and adaptive behavior -- 8. Learning disabilities -- 9. Classroom behavior and behavioral disorders -- Part 4. Assessment of academic skills -- 10. Reading -- 11. Mathematics -- 12. Writing -- 13. Oral language and the assessment of English learners -- Part 5. Important considerations -- 14. Including parents and families in the assessment process -- 15. Early childhood assessment -- 16. Assessment for transition education and planning.
Includes bibliographical references and index.
Keywords: ABILITY -- TESTING